Unraveling congenital ptosis with the aid of the pediatric perimeter device - Monika Thakur; Goura Chattannavar; Ranindita Saha; Himabindu Singh; Ramesh Kekunnaya; PremNandhini Satgunam (Indian Journal of Ophthalmology, 2023)
Background: Ocular morbidity with an early onset can have a significant impact on the long-term development of an individual. Hence, careful assessment of visual functions early on is very important. However, testing infants always poses a challenge. Standard tools to assess infants' visual acuity, ocular motility, and so on rely on the clinician's quick subjective judgments of an infant's looking behavior. Eye movements are usually observed from head rotations or spontaneous eye movements in infants. Judging eye movements in the presence of strabismus is even more challenging. Purpose: This video shows a 4-month-old infant's viewing behavior captured during a visual field screening study. The recorded video aided in the examination of this infant that was referred to a tertiary eye care clinic. The additional information captured through the perimeter testing is discussed. Synopsis: The Pediatric Perimeter device was developed to address visual field extent and gaze reaction time assessment in the pediatric population. As a part of a large-scale screening study, infants' visual fields were tested. During this screening, a 4-month-old infant presented with a ptosis in the left eye. The infant was consistently missing the light stimuli presented in the left upper quadrant in the binocular visual field testing. The infant was referred to a tertiary eye care center to a pediatric ophthalmologist for further examination. During clinical examination, the infant was suspected to either have congenital ptosis or monocular elevation deficit. But the diagnosis of the eye condition was unsure owing to the poor cooperation of the infant. With the aid of Pediatric Perimeter, the ocular motility was consistent with limitation of elevation in abduction, indicating a possible monocular elevation deficit with congenital ptosis. The infant was also noted to have Marcus Gunn jaw-winking phenomenon. The parents were assured and asked for a review in 3 months. In the subsequent follow-up, the Pediatric Perimeter testing was performed, and the recording showed a full extraocular motility in both eyes. Hence, the diagnosis was changed to only congenital ptosis. The probable explanation for missing the target in the left upper quadrant in the first visit is postulated further. The left upper quadrant is the superotemporal visual field of the left eye and the superonasal visual field of the right eye. As the left eye had ptosis, the superotemporal visual field could have been obstructed and hence the stimuli missed. The normative extent for the nasal and superior visual field is just about 30° for a 4-month-old infant. Hence, the right eye also perhaps missed the stimuli in its superonasal visual field extent. This video highlights the utility of the Pediatric Perimeter device in providing a magnified view of the infant's face along with greater visibility of ocular features from the infrared video imaging. This can potentially help the clinician to easily observe different ocular/facial abnormalities such as extraocular motility disorders, lid functions, and in identifying unequal pupil size, media opacities, and nystagmus. Highlights: The presence of congenital ptosis in younger infants might predispose as superior visual field defect and could also masquerade as a limitation in elevation. Video link: https://youtu.be/Lk8jSvS3thE